O impacto da pesca do camarão-rosa Farfantepenaeus paulensis (Perez-Farfante) (Decapoda, Penaeidae) nas assembléias de peixes e siris do Parque Nacional da Lagoa do Peixe, Rio Grande do Sul, Brasil - Loebmann, Daniel [UNESP]; Vieira, João Paes (FapUNIFESP (SciELO), 2006)
This work evaluates the impact of the pink shrimp Farfantepenaeus paulensis (Perez-Farfante, 1967) fishery on fish and crab assemblages of Lagoa do Peixe National Park, Brazil. We observed that composition of catches is similar to shrimp fisheries using fyke-net at others estuaries of Rio Grande do Sul State: pink shrimp (53%), accessory catches (24%) and bycatch (23%). However, fishery composition showed distinct differences along the saline gradient of the main park's lagoon. Regarding only fish species, the most impacted species in this fishery were Brevoortia pectinata (Jenyns, 1842), Micropogonias furnieri (Desmarest, 1823), and Jenynsia multidentata (Jenyns, 1842). In others estuaries from Rio Grande do Sul, in contrast, the most impacted species were M. furnieri, Genidens barbus (Lacepède, 1803) and Genidens genidens (Cuvier, 1829). The potential impact of the pink shrimp fishery at Lagoa do Peixe National Park seemed to be weaker when compared to shrimp fisheries elsewhere. We believe that the decision to prohibit this fishery at the Lagoa do Peixe National Park should not be based on its potential damage to the fish and crab assemblages but based on the simple fact that Brazilian laws do not allow fisheries inside National Parks.
The impact of the Pink Shrimp Farfantepenaeus paulensis (Perez-Farfante) (Decapoda, Penaeidae) fishery on the fish and crab assemblages of Lagoa do Peixe National Park, Rio Grande do Sul, Brazil
Keywords: Brevoortia pectinata; Bycatch; Conservation unit management; Estuaries; Micropogonias furnieri; Barbus; Decapoda (Crustacea); Farfantepenaeus paulensis; Genidens genidens; Jenynsia multidentata; Penaeidae